Mental practice in postgraduate training: a randomized controlled trial in mastoidectomy skills. Issue 1 (December 2016) - Conlin, Anne; Lea, Jane; Bance, Manohar; Chadha, Neil; Kilty, Shaun; Kozak, Frederick; Savage, Julian; Sidhu, Ravindar; Chen, Joseph; Westerberg, Brian
Abstract Background Mental practice, the cognitive rehearsal of a task in the absence of overt physical movement, has been successfully used in teaching complex psychomotor tasks including sports and music, and recently, surgical skills. The objectives of this study were, 1) To develop and evaluate a mental practice protocol for mastoidectomy 2) To assess the immediate impact of mental practice on a mastoidectomy surgical task among senior Otolaryngology─Head & Neck Surgery (OHNS) residents. Method Three expert surgeons were interviewed using verbal protocol analysis to develop a mastoidectomy mental practice script. Twelve senior Residents from Canadian training programs were randomized into two groups. All Residents were video-recorded performing a baseline mastoidectomy in a temporal bone lab. The intervention group received mental practice training, while the control group undertook self-directed textbook study. All subjects were then video-recorded performing a second mastoidectomy. Changes in pre- and post-test scores using validated expert ratings, the Task Specific Evaluation of Mastoidectomy and the Global Evaluation of Mastoidectomy, were statistically analyzed. Results A mental practice script was successfully developed based on interviews of three expert surgeon-educators. Task Specific Evaluation and Global Evaluation scores increased in both the mental practice and textbook study groups; there was no significant difference between the two groups in the change in scores post-intervention. There was a high and statistically signficant correlation between evaluators on the outcome measures. Conclusions We were not able to demonstrate a significant difference for the benefits of mental practice in mastoidectomy, possibly due to the sample size. However, mental practice is a surgical education tool which is portable, accessible, inexpensive and safe.